f(x) = 3x

^{2}- 2x -3f(x-1) =

I would really appreciate the steps and final outcome of this problem. Thank you!

f(x) = 3x^{2} - 2x -3

f(x-1) =

I would really appreciate the steps and final outcome of this problem. Thank you!

Tutors, please sign in to answer this question.

Aliquippa, PA

Dear Katelyn,

I'm not sure I understand this perfectly, but I think what you want is

f(x-1) = 3*(x - 1)^{2} - 2*(x - 1) - 3 = 3(x^{2} -2x + 1) - 2x + 2

f(x-1) = 3x^{2} -6x +3 -2x + 2 = 3x^{2} - 8x + 5

- Math 9861
- Algebra 1 4075
- Algebra 2 3503
- Word Problem 5119
- Math Help 5446
- Algebra Word Problem 2484
- Algebra Help 967
- College Algebra 1087
- Word Problems 1473
- Equations 706

## Comments

^{2}-8x+2. But I now I understand how to find the solution, so thank you for that!